Inside Cover: Oxidation Reactions with Bioinspired Mononuclear Non‐Heme Metal–Oxo Complexes (Angew. Chem. Int. Ed. 27/2016). Issue 27 (10th June 2016) - Engelmann, Xenia; Monte‐Pérez, Inés; Ray, Kallol
Abstract : Important oxidation reactions performed by biological systems are proposed to involve high‐valent Fe‐, Mn‐, and Cu‐oxo cores as reactive intermediates. The Review by K. Ray and co‐workers onpage 7632 ff. describes how recent advances in the generation, characterization, and reactivity of model Fe‐, Mn‐, and Cu‐oxo complexes can help in understanding how the steric and electronic properties of the metal centers modulate the reactivity of metalloenzymes.